Trial by ordeal as a mean of proof in court proceedings - Statkus, Rimgaudas; Kilčiauskas, Šarūnas; Talijūnas, Adomas (Vilnius University Open Series, 2024)
From today’s human perspective, trial by ordeal might seem barbaric, if not stupid. However, given the technological and social circumstances of the time, it was a quick, cheap and easy way to resolve complex cases and thus to ensure that justice was done in the medieval judicial process. The paper discusses the reasons for the emergence and disappearance of trial by ordeal in medieval Christian Europe, as well as the use of ordeals in the Grand Duchy of Lithuania and the legacy of the institute of trial by ordeal in the present-day judicial process in the Republic of Lithuania. The modern institution of the oath in the judicial proceedings of the Republic of Lithuania is examined as a legacy of the ritual oath of the Middle Ages. The hypothesis of the return of the institution of ordinals to the present-day Lithuanian law and why it would be impossible is also put forward.